What is The Association Between Low Serum Vitamin A Levels and The Risk of Developing Gestational Trophoblastic Disease - Yunike Putri Nurfauzia; I Made Adi Saputra Wijaya; Mutia Juliana; Yahya Nurlianto (The International Journal of Medical Science and Health Research, 2025)
Introduction: Gestational Trophoblastic Disease (GTD) comprises a group of disorders characterized by abnormal trophoblastic proliferation, including hydatidiform mole and gestational trophoblastic neoplasia (GTN). Vitamin A, known for its role in cellular differentiation and immune modulation, has been studied for its potential association with GTD risk and treatment outcomes. Methods: A systematic review of recent studies was conducted, focusing on serum vitamin A levels in GTD patients and the effects of vitamin A supplementation on treatment response. Included studies ranged from cross-sectional analyses to randomized controlled trials involving human subjects diagnosed with various GTD subtypes. Results: Ferraz et al. (2020) reported normal serum vitamin A levels (0.3–0.7 mg/dL) in patients with complete hydatidiform mole, indicating no association between low vitamin A levels and GTD risk. Conversely, Hidayat et al. (2020) demonstrated that vitamin A supplementation (6,000 IU/day) combined with methotrexate chemotherapy in low-risk GTN patients led to a more rapid decline in beta-human chorionic gonadotropin (β-hCG) levels and reduced chemotherapy resistance compared to chemotherapy alone. Discussion: While low serum vitamin A does not appear to predispose to GTD, supplementation may enhance chemotherapy efficacy, possibly through antioxidant and immunomodulatory mechanisms. However, limited sample sizes and study heterogeneity warrant further research. Conclusion: Vitamin A supplementation shows promise as an adjunct therapy in GTD treatment, improving outcomes in select patients, though it is not linked to disease risk. Larger, controlled studies are needed to confirm these findings